1984
DOI: 10.1093/rheumatology/23.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Beer Drinking and Its Effect on Uric Acid

Abstract: This study attempted to simulate the drinking habits of gout patients. Beer or squash was drunk over a 4-hour period on two successive days by five gouty and five normouricaemic men. Serum lactate increased with beer and squash, but elevation of plasma uric acid was confined to beer drinking. Urate clearance increased with both beverages, but 24-hour uric acid excretion was accentuated only by beer. The purine content of several beers was measured and the principal constituent found to be guanosine, which is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 0 publications
1
55
0
5
Order By: Relevance
“…An example of a non alcoholic component is the variation in purine content among different alcoholic beverages. 27,30 Beer is thought to be a risk factor for hyperuricemia because it is the only alcoholic beverage to have large purine content. 30 On the other hand, our finding suggests a possibility that alcohol beverage itself, rather than the type of alcoholic beverage, is responsible for the risk of hyperuricemia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of a non alcoholic component is the variation in purine content among different alcoholic beverages. 27,30 Beer is thought to be a risk factor for hyperuricemia because it is the only alcoholic beverage to have large purine content. 30 On the other hand, our finding suggests a possibility that alcohol beverage itself, rather than the type of alcoholic beverage, is responsible for the risk of hyperuricemia.…”
Section: Methodsmentioning
confidence: 99%
“…27,30 Beer is thought to be a risk factor for hyperuricemia because it is the only alcoholic beverage to have large purine content. 30 On the other hand, our finding suggests a possibility that alcohol beverage itself, rather than the type of alcoholic beverage, is responsible for the risk of hyperuricemia. Other previous studies have demonstrated that alcohol can elevate serum uric acid levels through increased uric acid synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…Extracts from yeast cell walls containing β-glucans can provoke severe arthritis in a breed of mice with genetic susceptibility, and antibiotic treatment targeting fungi is protective [69]. The association of alcohol consumption, and especially beer consumption [70], with gout could be due in part to the fact that beer is produced using brewers' yeast, Saccharomyces cerevisiae. Beer contains high levels of urate and can also contain ochratoxin, a mycotoxin produced by Saccharamyces [71].…”
Section: Disrupted Microbiome In Gout: Possible Rôle In Fungal Infectionmentioning
confidence: 99%
“…Øl ga høyest risiko for urinsyregikt og høyere enn brennevin, mens moderat vininntak ikke økte risikoen. Forskjellen forklares med ølets høye purinnivå (39).…”
Section: Alkoholunclassified